(untitled) (Indian Journal of Arid Horticulture, 2025)
Physico-chemical changes and economic shelf life of ber fruits cvs. Gola, Goma Kirti, Umran, Seb and Mundia were studied during storage at ambient temperature under semi-arid environment of Gujarat during the year 2001 and 2002. Increase in physiological loss in weight (PLW), spoilage percentage, total soluble solids, total sugar and reducing sugar and decrease in acidity and ascorbic acid with advancement of storage period were the general trends in all the cultivars. In the present study, Umran recorded the least physiological loss in weight (23.10%) and spoilage loss (20.10%) and exhibited 7 days economic shelf life. Goma Kirti could also be stored up to 7 days during storage. However, Gola recorded maximum physiological loss in weight and spoilage loss and showed only 3 days economic shelf life. In respect of storability, Seb proved to be better than Gola and could be stored up to 6 days at ambient temperature. The lowest rate of respiration rate (0.37 mg CO,/kg/h) was noted in Umran closely followed by Goma Kirti (0.41 mg CO/kg/h) however, Gola showed highest respiratory activity (0.56 mg CO,/kg/h) on the last day of storage.